Model recovery anti-windup for plants with rate and magnitude saturation - Forni, Fulvio; Galeani, Sergio; Zaccarian, Luca (ECC : 2009 European Control Conference : 23-26 August 2009, 2009)
In this paper two alternative approaches are provided to design an anti-windup compensator for control systems subject to limitations both in the magnitude and the rate of variation of the plant input. For both approaches, constructive numerical recipes are given and the relative merits are highlighted.